ANALYSIS OF LANGUAGE SKILLS IN PRIMARY SCHOOL CHILDREN (STUDY DEVELOPMENT OF CHILD PSYCHOLOGY OF LANGUAGE) - Dida Firmansyah (PrimaryEdu : Journal of Primary Education, 2018)
The skills and development of children's language are unique to observe, the researchers found several cases of varying language abilities in the age range of 6-12 years old who are still in primary school. From the perspective of child development psychology, the findings are influenced by several factors that are directly or indirectly related to the child's life. On the basis of this background, the researchers made an analysis of the results of observation of primary school children in the age range of 6-12 years with the object of research made randomly. The result of the data obtained by the researcher is that the elementary school age children have significant differences in the ability to speak in the school environment and outside the school environment.